2015
DOI: 10.1051/0004-6361/201526420
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of radio halos in galaxy clusters

Abstract: Context. Giant radio halos (RH) are diffuse Mpc-scale synchrotron sources detected in some massive and merging galaxy clusters. An unbiased study of the statistical properties of RHs is crucial to constraining their origin and evolution. Aims. We investigate the occurrence of RHs and its dependence on the cluster mass in a Sunyaev-Zel'dovich (SZ)-selected sample of galaxy clusters, which is nearly a mass-selected sample. Moreover, we analyse the connection between RHs and merging clusters. Methods. We selected… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
141
1
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 110 publications
(149 citation statements)
references
References 64 publications
6
141
1
1
Order By: Relevance
“…Sommer & Basu (2014) found that the selection of galaxy clusters from X-ray surveys biases against disturbed systems, thereby underestimating the fraction of radio halo clusters. Cuciti et al (2015) found a large fraction of radio halos in high-mass clusters, where most of them conform to the criteria of merging systems, following the morphological classification discussed in Cassano et al (2010).…”
Section: Introductionmentioning
confidence: 69%
“…Sommer & Basu (2014) found that the selection of galaxy clusters from X-ray surveys biases against disturbed systems, thereby underestimating the fraction of radio halo clusters. Cuciti et al (2015) found a large fraction of radio halos in high-mass clusters, where most of them conform to the criteria of merging systems, following the morphological classification discussed in Cassano et al (2010).…”
Section: Introductionmentioning
confidence: 69%
“…First results, based on a sub-sample of 57 clusters with available radio information, have been published in Cuciti et al (2015). We are completing the analysis of the sample using new GMRT and JVLA data of all the clusters that lack deep radio observations in order to determine the possible presence of diffuse emission.…”
Section: Introductionmentioning
confidence: 99%
“…ZwCl 2701 is a known relaxed galaxy cluster (Cuciti et al 2015;Kale et al 2015) positioned at RA = 09:52:49.20, DEC = +51:53:05.19 and located at a redshift of 0.214. The presence of X-ray cavities in this system have been reported by Rafferty et al (2006) in a broad study of a sample of 31 groups and cluster galaxies.…”
Section: Introductionmentioning
confidence: 99%